ANALISIS SENSITIVITAS PENDAPATAN USAHATANI KAKAO DI DESA BURANGA KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Utami, Sartika Sari; Yantu, M.R.; A., Sisfahyuni (AGROTEKBIS, 2013)
Cocoa is one of the plantation commodity which have a significant role in the national economy. This role can provide employment, income and foreign exchange. The purpose of this study was to ( i ) determine how the characteristics of cocoa farmers in the Buranga village Sub District Ampibabo District Parigi Moutong, (ii ) analyze the income of cocoa farming, and ( iii ) to determine the level of sensitivity of the income of cocoa farmers in the Buranga village Sub District Ampibabo District ParigiMoutong. Study location determinedintentionally (purposive). Determination of the respondents conducted by simple random method with 30 respondents. The analytical tool used in this research was the farm income analysisand sensitivity analysis. The results showed that the cocoa farm income on average Rp.10.271.755,56/ha. Results of iteration prices riseof cocoacounted by 5 % gives rise profit of Rp . 653,459.26 / Ha. On the other hand,decrease variable costs increaseprofit by Rp . 137,296.30ha. An increase in the price of cocoa by 15 % gives profit to riseby Rp .1,960,377.77/ha. On the other hand,decreasedvariable costs by 15 % increase the profits of Rp .411,888.89/ha.